Cyclic Pamidronate Infusion for Neonatal-onset Osteogenesis Imperfecta - Chia-Hsuan Lin; Yin-Hsiu Chien; Shinn-Forng Peng; Wen-Yu Tsai; Yi-Ching Tung; Cheng-Ting Lee; Chun-Ching Chien; Wuh-Liang Hwu; Ni-Chung Lee (Elsevier, 2014)
Patients with severe osteogenesis imperfecta (OI; MIM number 259420) suffer from low bone mass, fractures, and bone pain since birth, and have poor prognosis. This study assessed the outcome of patients with severe OI who were treated with cyclic pamidronate prior to the age of 1 year. Methods: The six patients, who had bone fractures either in utero or in their 1st month of life, were treated with cyclic pamidronate from a mean age of 2.8 months. Results: All the patients tolerated the infusion, except for having transient hypocalcemia at the first infusion. Decreases in irritability and improvements in feeding were observed 2-3 months after the first infusion. All patients showed a rapid increase in bone mineral density over the first 2 years. Fractures occurred at a rate of 0.6/year. At a mean age of 6.4 years, five patients with no interruption in treatment had normal ambulatory function, but they were short in height. Conclusion: Patients with neonatal OI can have a favorable outcome when treated with cyclic pamidronate infusions early in life.